Heracles in the Iberian Peninsula - Grzelak-Krzymianowska, Adriana (Collectanea Philologica, 2022)
The story of Herculesʼ achievements, like many others in Greek mythology, has undergone various changes since Hesiodʼs early transmissions helped to consolidate the essential elements of the myth and its characteristics. With the translocation of myths from Caucasian Iberia to Western Iberia, certain places, characters and events associated with the land were also transferred. The Fortunate Islands, the Garden of Hesperides, the place of the 10th and 11th labours of Hercules have been relocated, and the origin and meaning of the pillars set up by the hero have been identified and interpreted. The aim of this article is to show how one of these myths, namely that of Hercules and Geryon, was shaped in the classical and later periods. The transformation of three elements of this myth will be analysed: its location, the figure of Geryon and the description of Herculesʼ achievements.